Русский язык в воспоминаниях поляков, сосланных на территорию современного Пермского края в 1940-х годах (на материале выбранных воспоминаний) - Mikhalik, Elena (Acta Polono-Ruthenica, 2018)
The article deals with the problems of perceiving Russian language by the Poles deported during 1940th to the territory of the present-day Perm region as a result of mass deportations, as well as those arrested for taking part in the so called “anti-Soviet” activities and serving time in the camps of Perm region. While analyzing the texts of exiles’ memories the author comes to the conclusion that the Russian language for those Poles who survived through exposure to the Urals, is in the first place the language of enemy and captivity and serves as an instrument of propaganda and forced Russification. At the same time in some of the exiles’ memories studying of the Russian language is the only way to interact with the culture and literature which makes it easier to endure their spiritual isolation.